Abolitionist Music Theory and Marxism: Notes Toward a Reconciliation. (3rd February 2023) - Gopinath, Sumanth
Abstract: This essay offers a sympathetic Marxist commentary on Stephen Lett's "Making a Home of The Society for Music Theory, Inc." (2023 ). I explore questions of colonization and coloniality, which are viewed in literal, rather than metaphorical, terms; provide hypotheses about the political economy of contemporary US-American academic music theory, which seems to be inseparable from conflicts with composition; and meditate on theory's political futures in both practical and broader utopian-political ways.